Link Redundancy for High Availability Network based on OpenFlow Software Defined Network - Dyah Irawati, Indrarini; Hadiyoso, Sugondo; Sun Hariyani, Yuli (International Journal of Engineering and Technology, 2019)
Nowadays, Internet traffic is growing rapidly, as a result needed a realible network connectivity. The problem arise when the network is damage, i.e., link failure, server failure. It is important to create high availability network. This paper proposed link redundancy for high availability network based on OpenFlow Software Defined Network (SDN). OpenFlow supports port grouping for handling fast-failure while link broken. In this paper, we use cascade topology that consists 2-layer with 5 switches and emulate it using tools mininet and Ryu controller. The results for all scenario show that fast-failure method can detect link failure and recover without terminate the connection.Â